National Inuit Strategy on Research. - Unkn Unknown (Inuit Tapiriit Kanatami, 2018)
Strong public policies, informed by the best available evidence, can support optimal outcomes for Inuit that in turn benefit all Canadians. However, colonial approaches to research endure in Canada that prevent Inuit from making decisions about research activity in our homeland, such as setting the research agenda, monitoring compliance with guidelines for ethical research, and determining how data and information about our people, wildlife, and environment is collected, stored, used, and shared. In this time of reconciliation, research governance bodies, policies, and practices must be transformed to respect Inuit self-determination in Inuit Nunangat research. Advancing Inuit governance in research is imperative for enhancing the efficacy, impact, and usefulness of research for Inuit. This requires governments and research institutions to partner with Inuit representational organizations to implement engagement processes that respect the role of Inuit in decision-making when it comes to research involving our people, wildlife, and environment. This must occur at the regional, national, and international levels of Inuit governance. Since the 1990s, the Government of Canada has allocated hundreds of millions of dollars for research taking place in Inuit Nunangat, which is the Inuit-preferred name of the geographic, political, and cultural region whose various descriptions include “the Arctic”, “North”, and “North of 60” – none of which accurately encapsulate the Inuit homeland. The current investments in Inuit Nunangat research reflect a biological-physical science research bias that diminishes the prominence and attention given to other Inuit research priorities, such as health and social science. Moreover, federal research funding eligibility criteria tend to exclude Inuit representational organizations from accessing funding as lead institutions or principal investigators. This coupled with the absence of a university in Inuit Nunangat contributes to the continued domination of Inuit Nunangat research by non-Inuit researchers based outside of Inuit Nunangat. The purpose of the NISR is to address these challenges through coordinated actions that enhance the efficacy, impact, and usefulness of Inuit Nunangat research for Inuit. The NISR is domestic in scope yet it also acknowledges the international dimension of research on Inuit Nunangat. The objectives and actions that ITK is committed to implementing in partnership with Inuit representational organizations, governments, and research institutions, fall within five priority areas: 1) Advance Inuit governance in research; 2) Enhance the ethical conduct of research; 3) Align funding with Inuit research priorities; 4) Ensure Inuit access, ownership, and control over data and information; and 5) Build capacity in Inuit Nunangat research. The interrelated, interdependent nature of these priority areas requires a holistic, coordinated approach to implementing actions and evaluating progress. The NISR is intended to reach the stakeholders, such as governments, academia, and other research institutions, involved in Inuit Nunangat research. Inuit have brokered positive, mutually beneficial relationships with researchers and are also undertaking research ourselves. There is growing recognition within the research community about the partnership role that Inuit must play in Inuit Nunangat research. At the same time, important transformations must occur at the policy level for Inuit to achieve self-determination in research. Through the NISR, ITK will build on these advances, utilize existing governance processes and broker new partnerships to meet the needs of Inuit in research.